2011
DOI: 10.1016/j.trstmh.2011.02.002
|View full text |Cite
|
Sign up to set email alerts
|

‘Zoonoses? Not sure what that is…’ An assessment of knowledge of zoonoses among medical students in India

Abstract: This study focuses on estimating knowledge of zoonoses among medical students and recent graduates, with an aim of understanding critical gaps in medical education with respect to zoonoses. A semi-structured tool for knowledge assessment, having nine principal domains of knowledge and five domains of practice, was developed and validated. Using this tool, cross-sectional data was collected from 364 medical students and recent graduates and knowledge scores were calculated based on pre-defined guidelines. Out o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 11 publications
2
11
0
Order By: Relevance
“…This is similar to study conducted among medical practitioners (94.3%) in Tanzania [15] whereas it is much higher than that conducted among Indian medical interns and residents (5%) [16]. This variation may be due to study participant difference and rabies epidemiology in the studied areas.…”
Section: Discussionsupporting
confidence: 84%
“…This is similar to study conducted among medical practitioners (94.3%) in Tanzania [15] whereas it is much higher than that conducted among Indian medical interns and residents (5%) [16]. This variation may be due to study participant difference and rabies epidemiology in the studied areas.…”
Section: Discussionsupporting
confidence: 84%
“…14 Only 2.8% of medical students knew about rabies transmission by animals other than dogs in present study which was similar to a study done by Kakkar et al where only 5.5% of medical students correctly stated that rabies is transmitted by animals other than dogs. 15 Majority (91.8%) of medical students knew that the main mode of transmission of rabies by bites of rabid animal in current study which was near to a study conducted by Praveen et al where 97.7% of medical students knew that rabies is transmitted through bites of an animal. 11 Bhalla et al in their study observed that all the doctors were aware about animal bite as mode of transmission.…”
Section: Discussionsupporting
confidence: 54%
“…GPs and veterinarians are often the ‘first line’ responders when it comes to recognising, diagnosing, referring and/or treating such diseases in the face of an outbreak. Previous studies have shown that both veterinary and medical practitioners agree that cross professional collaboration can be useful in management of zoonoses [ 6 , [10] , [11] , [12] , [13] , [14] ]. However, in most countries there are no established pathways to facilitate collaboration and referral across current professional boundaries [ 6 , 15 ].…”
Section: Introductionmentioning
confidence: 99%